2018
DOI: 10.1002/ejoc.201800466
|View full text |Cite
|
Sign up to set email alerts
|

Laccase‐Based Oxidative Catalytic Systems for the Aerobic Aromatization of Tetrahydroquinazolines and Related N‐Heterocyclic Compounds under Mild Conditions

Abstract: In this work, for the first time, laccase (metalloenzyme)/3,5‐di‐tert‐butylcatechol (DTBC) as a new class of bioinspired quinone‐based cooperative catalytic oxidation system and laccase/2,2,6,6‐tetramethylpiperidine‐1‐oxyl (TEMPO) catalyst system were used for the aerobic oxidative synthesis of 2‐substituted quinazolines through cascade reaction of structurally divers aldehydes with 2‐aminobenzylamine. The products were obtained in good to high yields in phosphate buffer (0.1 m, 12.5 mL, pH = 4.5) and acetonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Quinazoline and quinazolin-4(3H)-ones are important nitrogen-containing heterocycles and the most convenient method for the synthesis of these valuable compounds is the cyclization of o -anthranilamides with aldehydes followed by subsequent oxidation [ 85 , 87 ]. Saadati et al reported a simple and efficient method for the synthesis of 2-substituted quinazolines through a cascade reaction of 2-aminobenzylamine and structurally diverse aldehydes via aerobic oxidative cyclization at pH 4.5 in the presence of laccase/3,5-di-tert-butylcatechol (DTBC) and laccase/TEMPO catalytic LMS ( Scheme 8 A).…”
Section: Application Of Laccases In Bio-oxidative Synthesis Of Heterocyclic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quinazoline and quinazolin-4(3H)-ones are important nitrogen-containing heterocycles and the most convenient method for the synthesis of these valuable compounds is the cyclization of o -anthranilamides with aldehydes followed by subsequent oxidation [ 85 , 87 ]. Saadati et al reported a simple and efficient method for the synthesis of 2-substituted quinazolines through a cascade reaction of 2-aminobenzylamine and structurally diverse aldehydes via aerobic oxidative cyclization at pH 4.5 in the presence of laccase/3,5-di-tert-butylcatechol (DTBC) and laccase/TEMPO catalytic LMS ( Scheme 8 A).…”
Section: Application Of Laccases In Bio-oxidative Synthesis Of Heterocyclic Compoundsmentioning
confidence: 99%
“…The oxidative system showed to be compatible with the presence of various substituents at different positions of the benzaldehyde ring and gave the desired products in moderate to high yields (40–96%). The same catalytic systems showed to be effective for the synthesis of other heteroaromatics such as quinoxaline, quinoline, indole and Hantzsch-type pyridine from aerobic dehydrogenation of their partial saturated precursors [ 87 ].…”
Section: Application Of Laccases In Bio-oxidative Synthesis Of Heterocyclic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…2- ( 4-Nitrophenyl ) quinazoline ( 3aq ) (CAS no. 80089-57-2) ( Saadati et al, 2018 ). Yellow solid, 375.5 mg, 50%; 1 H NMR (400 MHz, CDCl 3 ): δ 9.51 (s, 1H), 8.81 (m, 2H), 8.36 (m, 2H), 8.13 (m, 1H), 7.98 (m, 2H), 7.70 (m, 1H); 13 C{ 1 H} NMR (100 MHz, CDCl 3 ): δ 160.7, 158.9, 150.6, 149.2, 143.9, 134.6, 129.4, 128.8, 128.3, 127.2, 123.9, 123.8.…”
Section: Methodsmentioning
confidence: 99%
“…A further advantage is the specificity of the laccase-initiated reaction, which catalyse the amination and thiolation of para - and ortho -dihydroxylated aromatic compounds (Abdel-Mohsen et al 2014 ; Manda et al 2005 ; Niedermeyer et al 2005 ; Patel and Gupte 2018 ; Schlippert et al 2016 ; Wellington et al 2013 ). Further examples of useful modifications are laccase-mediated reactions in which two antibiotics containing a phenol moiety are combined (Agematu et al 1993 ), or where a phenolic compound is added into an antibiotic containing a phenolic moiety (Anyanwutaku et al 1994 ), or the synthesis or transformation of heterocyclic compounds (Mikolasch and Schauer 2003 ; Saadati et al 2018 ; Schäfer et al 2001 ; Youssef et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%